Dedicatoria - Bixler, Jacqueline Eyring; Palls, Terry L.; Garavito, Lucía; Seda, Laurietz; Reynolds, Bonnie Hildebrand; Burgess, Ronald D.; Cohen, Deb; Moreno, Iani del Rosario (Latin American Theatre Review, 1997)
Dedicatoria